Effects of CTGF Blockade on Attenuation and Reversal of Radiation-Induced Pulmonary Fibrosis. (9th March 2017) - Bickelhaupt, Sebastian; Erbel, Christian; Timke, Carmen; Wirkner, Ute; Dadrich, Monika; Flechsig, Paul; Tietz, Alexandra; Pföhler, Johanna; Gross, Wolfgang; Peschke, Peter; Hoeltgen, Line; Katus, Hugo A.; et al.
Abstract: Background: Radiotherapy is a mainstay for the treatment of lung cancer that can induce pneumonitis or pulmonary fibrosis. The matricellular protein connective tissue growth factor (CTGF) is a central mediator of tissue remodeling. Methods: A radiation-induced mouse model of pulmonary fibrosis was used to determine if transient administration of a human antibody to CTGF (FG-3019) started at different times before or after 20 Gy thoracic irradiation reduced acute and chronic radiation toxicity. Mice (25 mice/group; 10 mice/group in a confirmation study) were examined by computed tomography, histology, gene expression changes, and for survival. In vitro experiments were performed to directly study the interaction of CTGF blockade and radiation. All statistical tests were two-sided. Results: Administration of FG-3019 prevented (∼50%–80%) or reversed (∼50%) lung remodeling, improved lung function, improved mouse health, and rescued mice from lethal irradiation ( P < .01). Importantly, when antibody treatment was initiated at 16 weeks after thoracic irradiation, FG-3019 reversed established lung remodeling and restored lung function. CTGF blockade abrogated M2 polarized macrophage influx, normalized radiation-induced gene expression changes, and reduced myofibroblast abundance and Osteopontin expression. Conclusion: These results indicate that blocking CTGF attenuates radiation-induced pulmonary remodeling and can reverse the process after initiation. CTGF has a central role in radiation-induced fibrogenesis, and FG-3019 may benefit patients with radiation-induced pulmonary fibrosis or patients with other forms or origin of chronic fibrotic diseases.